CAMP a context-aware mobile portal. - Mandato, D. (IEEE Communications magazine)
Context-awareness-enhanced mobile computing is expected to be one of the major ingredients of the future wireless services based on IT technologies. This article proposes the concept of such a modular mobile Internet portal enhanced with context awareness features. Some services built into the portal are explained and the benefit for mobile users analyzed. A functional prototype is presented that has been successfully used as a concept proof